TREM-1 inhibitor specificity and timing of treatment initiation can impact its therapeutic efficacy in cancer and inflammatory disease - Sigalov, Alexander B. (Frontiers in Oncology, 2025)
BackgroundTriggering receptor expressed on myeloid cells 1 (TREM-1) is a key regulator in inflammation and an emerging therapeutic target in oncology and inflammatory disease.ObjectiveThis study aims to determine whether broad or macrophage-specific TREM-1 blockade demonstrates distinct therapeutic efficacy and superior outcomes in disease models.MethodsLigand-independent TREM-1 inhibitory peptides GF9 and GA31 (the latter in a form of macrophage-targeted lipopeptide complexes, GA31-LPC) were evaluated in animal models of pancreatic cancer, sepsis, pulmonary inflammation, and fibrosis. GF9 inhibits TREM-1 on all TREM-1-expressing cells, while GA31-LPC targets TREM-1 predominantly on macrophages.ResultsIn fully immunocompetent mice, GF9 and GA31-LPC alone significantly inhibited pancreatic cancer progression. In combination with anti-PD-L1 therapy, GA31-LPC, but not GF9, overcame cancer resistance to PD-L1 checkpoint blockade and synergized with immunotherapy. In PANC-1 xenograft-bearing athymic nude mice, both GF9 and GA31-LPC increased complete response rate and survival when combined with chemotherapy. The effectiveness of these agents was dependent on the timing of treatment initiation. GF9 was effective only when given with but not after chemotherapy. In contrast, GA31-LPC was effective only when given after but not together with chemotherapy. Inhibitor specificity and treatment timing effects of therapeutic TREM-1 blockade were also observed in sepsis and acute lung injury models, but not in fibrosis.ConclusionThese findings for the first time demonstrate that both inhibitor specificity and timing of treatment initiation are crucial for therapeutic TREM-1 inhibition. This has significant implications for clinical strategies targeting TREM-1, particularly informing tailored treatment approaches for cancer and inflammatory diseases.